PUBLIC PERCEPTION OF CENTRAL ASIAN MIGRANTS IN KAZAKHSTAN - Amriyeva, Yerkezhan (Nazarbayev University School of Sciences and Humanities, 2018)
Kazakhstan has become an attractive destination for many migrants from Central Asia, namely from Uzbekistan, Kyrgyzstan and Tajikistan. According to the International Organization for Migration, in 2016 the number of registered Central Asian migrants in Kazakhstan amounted to 1.2 million people, which is 5.5 % of total Kazakhstani population (IOM 2017, 17). Given the changing economic and demographic situation in the country, the topic of perception of migrants becomes especially salient. This study aims to reveal the perceptions of Kazakhstani people towards migrants from Central Asia, analyze the factors that might explain these perceptions and to understand their implications for inter-state relations and their variation across the ethnic lines...
ҚАЗАҚСТАНДАҒЫ ОРТАЛЫҚ АЗИЯ МИГРАНТТАРЫНА ҚОҒАМДЫҚ КӨЗҚАРАС
ОБЩЕСТВЕННОЕ ВОСПРИЯТИЕ МИГРАНТОВ ИЗ ЦЕНТРАЛЬНОЙ АЗИИ В КАЗАХСТАНЕ
Keywords: migrants; Central Asia